Semarang Citizens’ Culture And Psychosocial Behavior In Physical Activity At The Fitness Center - I Made Dwi Sastra Wargama; Soegiyanto Soegiyanto; Hadi Hadi (JUARA : Jurnal Olahraga, 2022)
With the lack of public knowledge in physical activities, some people worry and excessively do not have self-confidence; everyone has different attitudes, behaviors, personalities, and needs. The purpose of this study is to determine the culture and psychosocial behavior of Semarang City's citizens in carrying out physical activities at the fitness center. This study was done using the qualitative method. The purposive sampling techniques were used to determine the respondent and the data sources obtained from 29 respondents. The data was collected using observation, documentation, and interview techniques. Source triangulation, method triangulation, and peer discussion were used to check the validity of the data. Meanwhile, the data analysis procedure was done through the stages of various data sources, namely observation, interviews, and documentation. The result of this study is that the culture of doing physical activity in the fitness center of West Semarang District has moral, attitude, and physical aspects. For psychosocial, there are psychological and social aspects. From Ericson's eight stages of development, there are three groups of age stages, namely stage V Adolescent (12-20 years), stage VI Early Adult (20-40), and stage VII Middle Adult (40-65).